Is children's speech development changing? Preliminary evidence from Australian English-speaking 3-year-olds. (4th July 2022) - Holm, Alison; Sanchez, Katherine; Crosbie, Sharon; Morgan, Angela; Dodd, Barbara
Abstract: Purpose: Around 9% of children have difficulty acquiring intelligible speech despite typical sensory, neuro-motor and cognitive function. Speech-language pathologists (SLPs) rely on descriptions of children's speech errors to identify speech sound disorder (SSD) and determine intervention targets and goals. Existing normative data, however, need re-evaluation to reflect changes in populations and the language learning environment. This research evaluates whether developmental phonological patterns widely accepted as describing typical acquisition predict speech errors in a recent sample of pre-school children. Method: In 2015, 99 neurotypical children aged 3;0–3;8 years;months were assessed using the Diagnostic Evaluation of Articulation and Phonology (DEAP). Their performance was compared to studies describing speech development by children of the same age for phone repertoire and phonological patterns. Result: There were differences for both measures. Phone repertoire differences were marginal, but changes in phonological pattern use were unexpected. Suppression of three developmental phonological patterns (stopping of fricatives, final consonant deletion and voicing contrasts) was delayed compared to previous norms. Atypical consonant cluster reduction, sometimes considered a marker for disorder, was observed in 10% of children. Conclusion: There were qualitative differences in the speech development of the 2015 cohort of children compared to previous developmental norms. Valid and current normative data are necessary for the accurate identification of children needing intervention. The differences we found reinforce the need for regular updating of assessment tools, as well as greater understanding of how children's language learning environments are changing and potentially influencing speech development.